Transglutaminases in Dysbiosis As Potential Environmental Drivers of Autoimmunity - Lerner, Aaron; Aminov, Rustam; Matthias, Torsten (Frontiers in Microbiology, 2017)
Protein-glutamine γ-glutamyltransferases (transglutaminases) belong to the class of transferases. They catalyze the formation of an isopeptide bond between the acyl group at the end of the side chain of protein- or peptide-bound glutamine residues and the first order ε-amine groups of protein- or peptide-bound lysine. The transglutaminases are considered to be universal protein cross-linkers, and they play an essential role in a number of human diseases. In this review, we discuss mainly the bacterial transglutaminases in terms of the functionality of the enzymes and a potential role they may play in bacterial survival. Since microbial transglutaminases are functionally similar to the human homologs, they may be involved in the human disease provocation. We suggest here a potential involvement of transglutaminases in the pathologies such as autoimmune diseases. In this hypothesis, the endogenous microbial transglutaminases that are secreted by the gut microbiota, especially in a dysbiotic configuration, are potential drivers of systemic autoimmunity, via the enzymatic posttranslational modification of peptides in the gut lumen. These microbial transglutaminase activities directed towards cross-linking of naïve proteins can potentially generate neo-epitopes that are not only immunogenic but may also activate some immune response cascades leading to the pathological autoimmune processes.